Problems Faced by Teachers and Students in Teaching-Learning Geometry at Secondary Level - Tanzila Nabeel, Hina Noor, Kokab Nosheen (JSE, 2023)
Visually Impaired (VI) students confront a diversity of challenges in the area of learning Geometry. Such challenges create hurdles for visually impaired students to approach visual and tactile sense in learning Geometry. Diversity of challenges in spatial concepts of Geometry will continue to exist unless effort is directed to find the depth of these problems. This study was designed to explore the challenges of visually impaired students in learning Geometry at the secondary level.